Sinonasal adenoid cystic carcinomas accompanied by seromucinous hamartoma and/or atypical sinonasal glands arising from seromucinous hamartoma: insight into their histogenesis - Bradová, Martina; Agaimy, Abbas; Laco, Jan; Martínek, Petr; Ing, Stanislav Kormunda; Badoual, Cécile; Damjanov, Ivan; Leivo, Ilmo; Bacchi, Carlos E; Comperat, Eva; Ihrler, Stephan; Rupp, Niels J; et al. (Virchows Archiv, 2025)
The pathology of reactive, dysplastic, and neoplastic sinonasal seromucinous glands is complex, and their contribution to tumorigenesis of sinonasal carcinomas remains controversial. In our practice, we have observed the presence of respiratory epithelial adenomatoid hamartomas (REAH) and seromucinous hamartomas (SH) associated with adenoid cystic carcinomas (AdCC) in a subset of cases. In many of these cases, genuine atypical features and dysplastic characteristics of the glands were noted at the interface of SH and AdCC. To investigate this phenomenon further, 88 sinonasal AdCC cases were selected from the authors' files and analyzed histologically, immunohistochemically, and genetically searching for MYB/MYBL1 and NFIB gene fusions. HPV testing was also performed. Univariate statistical analysis was conducted on our cohort. Thirty-one cases (35%) showed features of atypical sinonasal glands arising in SH (ASGSH) at the SH-AdCC interface, characterized by bilayered epithelium, architectural disarray, mild nuclear polymorphism, and atypia, sometimes with colloid-like material in the lumen. The MYB immunomarker was negative in 14 ASGSHs (with a positive internal control in AdCC cells), while only two cases showed faint and moderate to weak expression of the antibody in ASGSH glands. In 12 cases, the immunostaining of ASGSH could not be properly assessed, while AdCC cells were negative. The immunostaining was not performed in five cases. Our findings suggest that a subset of sinonasal AdCC may originate in a multistep dysplastic process within SH, consistent with an SH-ASGSH-AdCC progression sequence.
Keywords: adenoidně cystický karcinom; protoonkogenní proteiny c-myb; MYBL1; Humans; lidé středního věku; Carcinoma, Adenoid Cystic; Adenoid cystic carcinoma; Atypical sinonasal glands arising in seromucinous hamartoma; Biomarkers, Tumor; Female; Aged; hamartom; dospělí; senioři; lidé; Immunohistochemistry; Paranasal Sinus Neoplasms; imunohistochemie; nádorové biomarkery; MYB; Adult; Proto-Oncogene Proteins c-myb; ženské pohlaví; Male; Middle Aged; Seromucinous hamartoma; Respiratory epithelial adenomatoid hamartoma; Aged, 80 and over; NFIB; senioři nad 80 let; mužské pohlaví; nádory vedlejších dutin nosních; Hamartoma